A reconnaissance across the Mackenzie mountains on the Pelly, Ross, and Gravel rivers, Yukon, and North West territories [electronic resource] - Keele, Joseph, 1863-1923.; Geological Survey of Canada. (Ottawa : Govt. Print. Bureau, 1910)
At head of title: Canada. Department of Mines. Geological Survey Branch . Also available in French under title: Reconnaissance à travers les montagnes Mackenzie sur les rivières Pelly, Ross et Gravel, Yukon et Territoires du Nord-Ouest. "Selected list of reports and maps . of special economic interest published by the Geological Survey": 7 p. at end. "No. 1097." Includes bibliographical references and an index. Electronic reproduction. Mode of access: Internet. 44